Eros - Antonioni, Enrica 1954-; Raben, Peer 1940-2007 (Artificial eye, 2009)
"Three world-class directors explore the deepest realms of sex, desire, and obsession in this luminous trilogy of films linked by theme of erotic passion. Wong Kar-Wai's ravishing drama 'The Hand', set in 1960s Hong Kong, tells of the achingly unrequited relationship between a tailor (Chang Chen) and a beautiful courtesan (Gong Li). Stephen Soderbergh writes and directs the wryly comic 'Equilibrium' in which Robert Downey Jr.s anxious ad executive describes a mysterious dream woman to his preoccupied psychiatrist (Alan Arkin). Finally, in Italian legend Michelangeolo Antonioni's beautiful 'The Dangerous Thread of Things', an estranged couple embark on an erotic and sensual journey." [amazon.de]
Original: USA, Italien, Hong Kong, Frankreich, Luxemburg, Großbritannien 2004
Enhanced for widescreen TVs
Special features: theatrical trailer and filmographies
Keywords: Film; DVD-Video